Linking Employee Engagement and Employee Retention: The Roles of Job Satisfaction and Work-Life Balance in Manufacturing Industries - Sri Mulyati; Rosma Debi; Andre Lesmana; Pilda Agustin (DPPM Universitas Pelita Bangsa, 2025)
This study investigates the influence of employee engagement on employee retention, mediated by job satisfaction and moderated by work-life balance. Employing a quantitative approach with 76 respondents from a manufacturing company in Cikarang, data was collected via questionnaires and analyzed using Partial Least Squares (PLS). Results indicate that employee engagement significantly impacts job satisfaction, and work-life balance significantly affects employee retention. However, the direct influence of employee engagement and job satisfaction on retention, as well as the mediating effect of job satisfaction, were not significant. This finding implies that job satisfaction, although traditionally viewed as a strong predictor of retention, may not always function as a mediator in specific organizational contexts, particularly among operational-level employees, thereby extending the discourse in HRM theory regarding conditional mediating mechanisms. Nevertheless, 85.3% of the variability in employee retention can be explained by these variables. From a managerial perspective, this highlights the importance for firms to prioritize strategies that foster engagement and promote healthy work-life balance, as these factors directly contribute to retention even when job satisfaction does not mediate the relationship. Companies are advised to focus on improving employee engagement and work-life balance to support employee retention. This journal explores how employee engagement and work-life balance influence employee retention in the manufacturing sector, with job satisfaction as a mediator, finding both factors to be important despite the non-significant mediating role of job satisfaction.